2014
DOI: 10.4161/15384047.2014.986967
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine resistant pancreatic cancer cell lines acquire an invasive phenotype with collateral hypersensitivity to histone deacetylase inhibitors

Abstract: Gemcitabine based treatment is currently a standard first line treatment for patients with advanced pancreatic cancer, however overall survival remains poor, and few options are available for patients that fail gemcitabine based therapy. To identify potential molecular targets in gemcitabine refractory pancreatic cancer, we developed a series of gemcitabine resistant (GR) cell lines. Initial drug exposure selected for an early resistant phenotype that was independent of drug metabolic pathways. Prolonged drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 30 publications
(39 reference statements)
1
35
0
Order By: Relevance
“…In addition, PANC‐1 SP cells also exhibited enhanced migratory and invasive abilities as compared with non‐SP and parental cells. In agreement, a recently study where a series of gemcitabine resistant pancreatic cancer cell lines, which were developed by prolonged gemcitabine exposure, demonstrated up to a 15‐fold increase in invasive potential that directly correlates with the level of gemcitabine resistance . These findings suggest a mechanistic relationship between chemoresistance and metastatic potential in pancreatic cancer stem cells; it also implicates that molecular pathway governing the generation and maintenance of SP cells can be exploited for developing therapeutic strategies against refractory and drug‐resistant pancreatic cancer.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, PANC‐1 SP cells also exhibited enhanced migratory and invasive abilities as compared with non‐SP and parental cells. In agreement, a recently study where a series of gemcitabine resistant pancreatic cancer cell lines, which were developed by prolonged gemcitabine exposure, demonstrated up to a 15‐fold increase in invasive potential that directly correlates with the level of gemcitabine resistance . These findings suggest a mechanistic relationship between chemoresistance and metastatic potential in pancreatic cancer stem cells; it also implicates that molecular pathway governing the generation and maintenance of SP cells can be exploited for developing therapeutic strategies against refractory and drug‐resistant pancreatic cancer.…”
Section: Discussionsupporting
confidence: 77%
“…The latter cell line shows similar invasive characteristics and morphology as seen in HepG2S1 cells although without the typical marker expression profile of EMT [25]. In vitro, monotherapy with acriflavine at increased dose, was cytotoxic for all cell lines tested.…”
Section: Resultsmentioning
confidence: 76%
“…Gene expression of the different lines was repeatedly determined over time by qRT-PCR and compared to transcriptome data of cells early after they were obtained from ATCC, this to monitor stability. The gemcitabine resistant human pancreatic cancer cell lines MiaPaCa-2 GR800 and their parental cell line MiaPaca-2 were a kind gift of Prof. T. Landowski [25] and were used to investigate the effect of ACF on drug sensitivity by XTT cell viability assay as described below.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the selection of CDA overexpression in response to prolonged drug exposure is responsible for resistance to gemcitabine (18,43) and that the ectopic expression of CDA in CDA-deficient cancer cells leads to a significant increase in resistance to gemcitabine (18,44). We thus evaluated the functionality of the CDA protein produced after 5-Aza-dC treatment by breast and ovarian cancer cells, HCC-1954 and IGROV-1, respectively.…”
Section: Cda Is Downregulated By Dna Methylationmentioning
confidence: 99%